Examining the moderating effect of inconsistent reviews and its gender differences on consumers’ online shopping decision - Zhang, Kem Z.K.; Cheung, Christy M.K.; Lee, Matthew K.O. (International journal of information management, 2014)
•This study examines the role of inconsistent reviews in online shopping decision.•We examine its moderating effect and gender differences in a trust-based model.•Cognitive trust affects emotional trust, which further leads to purchase intention.•Emotional trust affects purchase intention more in the inconsistent review context.•The moderating effect of inconsistent reviews is stronger for female consumers. The prevalence of social media has provided consumers with many opportunities to post online reviews on a wide range of products on the Internet. In this study, we attempt to investigate the moderating effect of inconsistent reviews (i.e., a mix of positive and negative reviews) on consumers’ purchase decision. We further examine whether the effect will differ from female to male consumers. We explain the moderating effect and its gender differences based on the theory of reasoned action, trust literature, and information processing literature. The research hypotheses are empirically tested in a laboratory experiment using structural equation modeling approach. Our findings show that consumers’ cognitive trust to online retailers affects emotional trust, which further leads to purchase intention. When consumers are exposed to inconsistent reviews, the influence of emotional trust on purchase intention is significantly stronger. Moreover, the moderating effect of inconsistent reviews is stronger for female consumers than for male consumers. We expect that this study can enrich the understanding of how inconsistent reviews play a role in consumers’ online shopping decision. Online retailers may apply our findings and leverage the influence of online consumer reviews in social media. Implications for both researchers and practitioners are discussed.